"Community Cup, We Are a Big Family": Examining Social Inclusion and Acculturation of Newcomers to Canada through a Participatory Sport Event - Rich, Kyle A. (Social Inclusion, 2015)
While sport is widely understood to produce positive social outcomes for communities, such as the inclusion of diverse and marginalized groups, little researched has focused on the specific processes through which these outcomes may or may not be occurring. In this paper, we discuss the Community Cup program, and specifically a participatory sport event which seeks to connect newcomers to Canada (recent immigrants and refugees) in order to build capacity, connect communities, and facilitate further avenues to participation in community life. For this research, we worked collaboratively with the program to conduct an intrinsic case study, utilizing participant observation, document analysis, focus group, and semi-structured interviews. We discuss how the structure and organization of the event influences participants’ experiences and consequently how this impacts the adaptation and acculturation processes. Using Donnelly and Coakley's (2002) cornerstones of social inclusion and Berry’s (1992) framework for understanding acculturation, we critically discuss the ways that the participatory sport event may provide an avenue for inclusion of newcomers, as well as the aspects of inclusion that the event does not address. While exploratory in nature, this paper begins to unpack the complex process of how inclusion may or may not be facilitated through sport, as well discussing the role of the management of these sporting practices. Furthermore, based on our discussion, we offer suggestions for sport event managers to improve the design and implementation of programming offered for diverse/newcomer populations.